How to gear up against cyber crime.
According to a recent report from Lloyds Banking Group, a major cyberattack could cost the world up to EUR 46 billion. This raises an important question : how can financially motivated cybercrime be deterred? The E-CRIME project is providing concrete answers with a focus on non-ICT sectors.